Impact of Overgrazing on The Grasslands - Shankarnarayan, K A (Annals of Arid Zone, 2016)
Overgrazing in grasslands results in slow but inexorable deleterious change in botanical composition which however varies with the type of grass t:over, its palatability, forage productivity and the way in which it is utilised and the sequence of climatic events'. It triggers off succession and invariably the degenerated stage Consists of inferior less palatable perennials and annuals such as Oroperium thomeaum, Aristida adscensionis and Eragrostis unioloides accompanied by reduction in the per cent cover of the desirable species. The physiognomy and growth of the desirable species are also affected from "basket" to "saucer" shape which are strongly influenced by grazing and soil moisture relations. The impact of browsing is nowhere more pronounced than in top feed trees such as Zizyphns nummularia, Salvadora oleoides which assume "bush form" whereas Prosopis cineraria and Anogeissus pendula become "pillow cushion" form. The dynamics of herbage production is influenced by the severity of grazing which is attributed to the destruction of shoot apex resulting in lowered growth rate as evidenced in Lseilema laxum, C. ciliaris, C. setigerus and Sehima nervosum grasslands. Concurrently the root biomass and root number also get decreased with overgrazing. Heavy intensity of grazing on Lasiurus-Aristida rangeland showed lowest weight gains in Tharparker yearling heifers both in low and medium rainfall regime The trampling by hooves of stock appear more damaging leading to disintegration of humus and organic matter and altering the mechanical composition of the soils. The hydrology is drastically impaired with high bulk density, lower infiltration and increased runoff. Overgragzing in grassland gave maximum runoff. (27%) and maximum soil loss (2100 lb/acre). Likewise in land use having overgrazed fallow the runoff was 22% but soil loss was as high as 2029 lb/acre.